Effects of Antioxidants in Fermented Beverages in Tissue Transcriptomics: Effect of Beer Intake on Myocardial Tissue after Oxidative Injury - Alex Gallinat; Gemma Vilahur; Teresa Padro; Lina Badimon (MDPI AG, 2023)
Fermented beverages, such as wine and beer, are rich in polyphenols that have been shown to have protective effects against oxidative stress. Oxidative stress plays a central role in the pathogenesis and progression of cardiovascular disease. However, the potential benefits of fermented beverages on cardiovascular health need to be fully investigated at a molecular level. In this study, we aimed at analyzing the effects of beer consumption in modulating the transcriptomic response of the heart to an oxidative stress challenge induced by myocardial ischemia (MI) in the presence of hypercholesterolemia in a pre-clinical swine model. Previous studies have shown that the same intervention induces organ protective benefits. We report a dose-dependent up-regulation of electron transport chain members and the down-regulation of spliceosome-associated genes linked to beer consumption. Additionally, low-dose beer consumption resulted in a down-regulation of genes associated with the immune response, that was not shown for moderate-dose beer consumption. These findings, observed in animals having demonstrated beneficial effects at the organ-level, indicate that the antioxidants in beer differentially affect the myocardial transcriptome in a dose-dependent manner.